A Comprehensive, Epidemiological and Ecological Descriptive Study on Vitamin D Status in Iran (308005 People, from 2009-2018) - Dariush D. FARHUD; Atefeh MEHRABI; Abdolfattah SARAFNEJAD; Hamid Reza SADEGHIPOUR; Abbas RAHIMIFOROUSHANI; Mohammdad Bagher ROKNI; Keyvan MAJIDI; Ahad ALIZADEH; Marjan ZARIF-YEGANEH; Maryam JALALI; Mahmoud JALALI; Ali Akbar AMIR ZARGAR; et al. (Tehran University of Medical Sciences, 2019)
Background: Vitamin D is an essential substance for absorption of calcium and phosphorus from intestine so it is vital for muscles and skeletal development. Deficiency of this vitamin is pandemic. The vitamin D status depends on the different factors such as UV exposure, diet, and ecological features of living location, age and gender. The aim of this study was to describe the vitamin D level in different provinces of Iran and to investigate the association between vitamin D status and multiple variables. Methods: We collected the serum 25(OH)D (Vitamin D) level data of 308,005 people referred to different laboratories from 30 provinces of Iran and organized them by each province, year, age, gender, precipitation, latitude and longitude, and humidity over 10 yr (2009-2018). Data were analyzed to find out the correlation between age, gender, longitude and latitude, humidity and sum of precipitation. Results: West Azerbaijan had the highest level of vitamin D with a mean level of 33.24 and a standard deviation of 32.001, and North Khorasan had the lowest level with a mean level of 14.46 and a standard deviation of 8.980 among 30 provinces of Iran. The correlation between all studied variables (age, and gender, latitude and longitude, humidity, the sum of precipitation) was significant (P<0.001). Conclusion: The average total vitamin D level in Iran is 25.41 ng/ml, which is within the area of deficiency. Vitamin D is associated with age, and gender, latitude and longitude, humidity, the sum of precipitation. So changes in any of these variables can lead to vitamin D alteration.